Changes in isokinetic strength throughout the annual training cycle in elite youth soccer players - Lehnert, M.; Chvojka, P. (The 3rd Wingate Congress of Exercise and Sport Sciences, 2014)
Muscle strength is an important factor in soccer from a performance and health perspective. A great number of studies have focused on the evaluation of isokinetic strength of knee flexors and extensors in soccer players. However, it remains to be identified how muscle strength of the knee flexors and extensors are altered throughout the annual training cycle in elite youth male soccer players. The aim of the study was to investigate the seasonal variation in the strength of the knee flexors and extensors in highly trained youth soccer players. The players (n=16; age 16.7±0.7) who played in the Czech U17 first league were measured at the end of the competitive season, at the beginning of the off-season and during the sixth week of a new competitive season. Isokinetic concentric peak torque was measured at 60°•s-1, 180°•s-1, 360°•s-1 in a sitting position using an isokinetic dynamometer IsoMed 2000 (D. & R. Ferstl GmbH, Hemau, Germany). The testing range of motion was set from 10-90° of knee flexion. After warm-up players performed a set of six maximal repetitions for both dominant and non-dominant limb. The rest time during the measurements at different velocities was 1 minute and the rest time between the measurement of the right and left leg was 3 minutes. Average values of peak torque significantly changed during the observed periods. Significant differences (p<0.05) between the three measurement sessions were noted with respect to the knee flexors at all angular velocities. A post hoc test confirmed a significant increase between the first and second measurements for flexion in both dominant (180°•s-1; p=0.033) and non-dominant legs (360°•s-1; p=0.004). A significant increase was also found between the first and third measurements for both limbs during knee flexion (60°•s-1). The results of the study indicate that isokinetic strength of the knee flexors and extensors changed in elite youth soccer players who were actively involved in an annual training cycle at a professional soccer club. However, the changes in PT values of the knee flexors and extensors are highly variable depending on muscle group and movement velocity. Our findings do not support the view that traditional soccer training in youth soccer players produces a quadriceps dominant athlete.